2002
DOI: 10.1002/cncr.10675
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in cancer prevalence in Connecticut, Iowa, and Utah

Abstract: BACKGROUNDCancer prevalence—the proportion of a population with cancer, including those recently diagnosed, those in treatment, and survivors—is an important indicator of future health care requirements. Only limited information on cancer prevalence is available for the United States. In particular, comparative interstate studies are not available. In this study, we estimate and analyze the prevalence of seven major cancers in Connecticut, lowa, and Utah using the tried and tested PREVAL method applied to Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Table IV reports estimates of female breast cancer prevalence from di erent sources for comparison. PIAMOD estimates are fully consistent with estimates derived from CTR data, that is, by using the counting method PREVAL (PREVALence) (Micheli et al, [26]), and the method by Feldman [2], as reported in references [27,28]. Conversely, prevalence estimates derived by the U.S. National Health Interview Survey (NHIS) [27] for 1997 appear to be grossly underestimated with respect to any other method.…”
Section: Application To Breast Cancer Prevalence In Connecticutmentioning
confidence: 67%
“…Table IV reports estimates of female breast cancer prevalence from di erent sources for comparison. PIAMOD estimates are fully consistent with estimates derived from CTR data, that is, by using the counting method PREVAL (PREVALence) (Micheli et al, [26]), and the method by Feldman [2], as reported in references [27,28]. Conversely, prevalence estimates derived by the U.S. National Health Interview Survey (NHIS) [27] for 1997 appear to be grossly underestimated with respect to any other method.…”
Section: Application To Breast Cancer Prevalence In Connecticutmentioning
confidence: 67%
“…1,2 It has been estimated that increasing use of adjuvant chemotherapy could contribute up to one-fifth of the 49% projected reduction in mortality by 2020. 3 Although colorectal cancer is most common in elderly patients, 4,5 and despite the effectiveness of 5-fluorouracil (5FU)-based therapy, patients aged 65 and older usually do not receive chemotherapy. 1 Specifically, only 52% of older node-positive colon cancer patients undergo adjuvant therapy after surgical resection, in spite of it being the standard of care to treat Stage III colon cancer since 1990.…”
mentioning
confidence: 99%
“…• Total prevalence is defined as everyone alive on a given date who has ever been diagnosed with cancer in their lifetime, regardless of whether or not they have been cured or are currently in relapse [4][5][6].…”
Section: Introductionmentioning
confidence: 99%